2023
DOI: 10.1101/2023.02.16.528878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into the UFM1 E3 ligase complex in ufmylation and ribosome-associated protein quality control

Abstract: Ubiquitin-fold modifier 1 (UFM1) is a ubiquitin-like protein covalently conjugated with intracellular proteins through ufmylation, similar to ubiquitylation. Ufmylation is involved in processes such as endoplasmic reticulum (ER)-associated protein degradation, ribosome-associated protein quality control (RQC) at the ER (ER-RQC), and ER-phagy. However, it remains unclear how ufmylation regulates such distinct ER-related functions. Herein, we provide insights into the mechanism of the UFM1 E3 complex in not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…3E). As reported previously, the C-terminal 40 amino acids harbor a UFL1 binding site (34), but its deletion did not completely abolish UFL1 binding, consistent with another study showing an interaction between UFBP1 and UFL1 independent of this sequence (21). Cellbased UFMylation assay showed that overexpression of UFBP1 or the UFBP1ΔC mutant did not reduce α-Syn UFMylation (fig.…”
Section: Overexpression Of Ufbp1 Stimulates α-Syn Secretionsupporting
confidence: 91%
“…3E). As reported previously, the C-terminal 40 amino acids harbor a UFL1 binding site (34), but its deletion did not completely abolish UFL1 binding, consistent with another study showing an interaction between UFBP1 and UFL1 independent of this sequence (21). Cellbased UFMylation assay showed that overexpression of UFBP1 or the UFBP1ΔC mutant did not reduce α-Syn UFMylation (fig.…”
Section: Overexpression Of Ufbp1 Stimulates α-Syn Secretionsupporting
confidence: 91%
“…Still, other interactions, either in the context of the trimolecular ligase complex, other ER membrane proteins, or the ER-associated ribosomes, are likely to contribute. It is noteworthy that while structural and functional data obtained in cells transfected with the interacting partners convincingly identify the ER-associated active ligase as a trimolecular complex of UFL1 with DDRGK1 and C53 30,31 , very little is known about the assembly of the endogenously expressed partners in cells. We found that catalytically active and inactive BPLF1 are coprecipitated by endogenously expressed UFL1, DDRKG1, and C53, but only DDRGK1 coprecipitated UFL1 and C53.…”
Section: Discussionmentioning
confidence: 99%
“…The UFMylation machinery is recruited to the ER by the adaptor protein DDRGK1 (also known as UFBP1) 27,29 . The interaction with DDRGK1 activates the E3 ligase 30,31 . In addition, the activity of the ligase is regulated by binding to CDK5RAP3 (also known as LZAP/C53, hereafter C53) 30,31 , which also serves as a speci c receptor for ribosome stress-induced ER-phagy 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While UFC1 and UBA5 are freely present in the cytosol, UFL1 is associated with the ER membrane through its interaction with DDRGK1 (Liang et al , 2020). Additionally, recent findings indicate that LZAP, another partner of the UFL1‐DDRGK1 complex, also possesses a UFM1 binding site (Ishimura et al , 2023). This further assists in bringing UFC1 ~ UFM1 in proximity to UFL1, enhancing its ability to outcompete UBA5.…”
Section: Discussionmentioning
confidence: 99%